Profil Penguasaan Konsep Tatanama Senyawa dan Persamaan Reaksi Pada Siswa Kelas XI IPA-4 SMA Negeri 2 Sampit Tahun Ajaran 2018/2019 - Dwi Azarianti; I Made Sadiana; Nopriawan Berkat Asi (FKIP Universitas Palangka Raya, 2020)
The concept of compound nomenclature and reaction equation is one of the chemical concepts taught in high school class X. This study aims to describe the mastery of the concept of compound nomenclature and reaction equations in class XI students. This research is a descriptive qualitative research. The subjects of this study were 30 students of class XI IPA-4 of SMA Negeri 2 Sampit in the 2018/2019 school year who had received compound nomenclature learning and reaction equations. Data collected in the form of RPP documents obtained from chemistry teachers, students' concept mastery data obtained through the description test with a total of 14 items from 4 indicators and data from student interviews. The results showed that students' mastery of concepts on the topic of compound nomenclature and student reaction equations that amounted to 74.18% were in the high category. Mastery of student concepts is divided into 3 (three) categories, namely very high, high, and moderate. Students in the very high category numbered 9 students, students in the high category numbered 12 students. Students in the medium category numbered 9 students. Students are able to write molecular formulas and empirical formulas of compounds of 81.66% with a high category, students are able to write the names of inorganic compounds and organic compounds by 75.18% with high categories, students are able to write chemical formulas of simple inorganic compounds and simple organic compounds of 84.58% with a high category and students are able to explain portions of a reaction equation of 47.92% with a low category.